The effects of multiple job holding and employee well-being on primary job performance of public sector workers in the volta region of Ghana - Dzineku, William K; Niekerk, T Van; Dzansi, D Y (International Journal of Management and Sustainability, 2025)
The study investigates the impact of holding multiple jobs and employee well-being on primary job performance among public sector workers in Ghana. Multiple job holdings (MJH) are becoming more common among Ghana’s public sector personnel, owing in part to economic concerns. However, this phenomenon has substantial consequences for such employees’ well-being and primary job performance. To better understand the complexities of MJH and its influence on public sector personnel in Ghana’s Volta Region, this study employs a variety of academic frameworks, including role balance theory (RBT) and job demand theory. In light of these theoretical frameworks, the study investigated many MJH-related variables, such as primary job performance, employee well-being, and drives. This study used a quantitative research method that included a cross-sectional survey design to investigate the impact of multiple job holdings (MJH) on public sector employees in Ghana’s Volta Region. 1,198 public sector staff in the Volta Region completed a systematic questionnaire. The acquired data was transcribed, coded, and examined. The study’s findings indicate that changes in employee well-being have a positive impact on primary job performance. Furthermore, the study observed that MJH significantly contributed to the prediction of changes in employee well-being. However, MJH had a statistically insignificant positive effect on primary job performance, implying that it may not improve primary job performance among public sector employees in this study.